The National Average is a D: Who is to Blame? - Collie-Patterson, Janet Maria (International Journal of Bahamian Studies, 2008)
The publishing of the Bahamas General Certificate of Secondary Education (RGCSE) 2005 examination results sparked much debate about the national average being a D. Much of the debate was focused on the teacher and the school whilst very little was said about the other contributors to achievement in education. In her 1999 study of 1,036 students and 52 teachers from public and private schools in New Providence, Collie-Patterson found the students’ characteristics consisting of student’s prior ability, attitude toward school, socioeconomic status and parental involvement make the largest contribution (60%) to mathematics achievement. Taken individually, the effect size indicated that student’s prior ability made the largest contribution (48%) to mathematics achievement. The set of teachers’ characteristics, including professional development, teaching experience, and educational background, were significantly related to mathematics achievement and contributed only 8% to students’ mathematics achievement. The set of classroom characteristics contributed 35% to mathematics achievement and the set of schools’ characteristics contributed 12% to mathematics achievement. The purpose of this paper is to analyze the factors that could potentially influence student performance in mathematics which greatly affects the national average due to the large number of students taking the mathematics examination and the low grade point average of that examination.